2009
DOI: 10.1002/lt.21953
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sirolimus on the recurrence of hepatocellular carcinoma after liver transplantation

Abstract: Tumor recurrence after liver transplantation for hepatocellular carcinoma is associated with a poor prognosis. Because immunosuppression is a well-known risk factor for tumor growth, it is surprising that its possible role in the outcome of liver transplantation has been poorly evaluated. We performed a case-control review of prospectively collected data and compared 2 groups of patients according to the type of immunosuppression after liver transplantation for hepatocellular carcinoma at a single center. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
139
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(147 citation statements)
references
References 28 publications
(34 reference statements)
4
139
1
3
Order By: Relevance
“…Although the data remain preliminary, a series of uncontrolled trials have shown markedly lower rates of HCC recurrence after liver transplantation in patients receiving sirolimus-based immunosuppression versus a standard CNI regimen. [45][46][47][48] Chinnakotla et al 45 documented a 5-year survival rate of 80% in 121 patients receiving sirolimus after they underwent liver transplantation for HCC and a 5-year survival rate of 59% in 106 case controls receiving a CNI (P ¼ 0.001). In a large registry analysis of 2491 patients who underwent transplantation for HCC, sirolimus-based maintenance therapy was also associated with improved survival and conferred a 15% 5-year survival advantage in comparison with CNI-based immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data remain preliminary, a series of uncontrolled trials have shown markedly lower rates of HCC recurrence after liver transplantation in patients receiving sirolimus-based immunosuppression versus a standard CNI regimen. [45][46][47][48] Chinnakotla et al 45 documented a 5-year survival rate of 80% in 121 patients receiving sirolimus after they underwent liver transplantation for HCC and a 5-year survival rate of 59% in 106 case controls receiving a CNI (P ¼ 0.001). In a large registry analysis of 2491 patients who underwent transplantation for HCC, sirolimus-based maintenance therapy was also associated with improved survival and conferred a 15% 5-year survival advantage in comparison with CNI-based immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…67 When sirolimus is used for immunosuppression after transplant in HCC patients, multiple retrospective studies and case reports have revealed trends of lower recurrence rate and metastasis of HCC after LT. [68][69][70][71][72][73][74][75][76][77][78] However, the timing of when to start mTOR inhibitors after LT is debatable, particularly with early reports of hepatic artery thrombosis when sirolimus is used immediately after transplant. 79,80 It is also unclear if mTOR should be used at the time of HCC recurrence.…”
Section: Sirolimusmentioning
confidence: 99%
“…58,59,61,[89][90][91] Alternatively, there have been several smaller prospective studies on sirolimus, which showed encouraging results in LT patients at high risk for HCC recurrence when used as the de novo immunosuppressive agent and in combination with tacrolimus, in addition to the many retrospective studies, which revealed beneficial outcomes in patients on sirolimus for immunosuppression who have recurrent HCC. [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] While promising, there are many unanswered questions regarding the use of sorafenib and sirolimus such as the timing of their introduction after transplant and the length of treatment. Prospective randomized controlled studies evaluating the immunosuppressive regimen in HCC patient's undergoing LT, as well as treatment modalities for recurrent HCC including surgical approaches and systemic chemotherapies are eagerly anticipated in the near future.…”
Section: Sorafenibmentioning
confidence: 99%
“…Established predictors for HCC recurrence after transplantation are tumor-specific factors (tumor size, number of malignant nodules, presence of microsatellites and vascular invasion) as well as α-fetoprotein levels before transplantation [29,30] (that were normal in this case) and immunosuppression levels [31,32] . A meta-analysis on pre-transplant risk factors for HCC recurrence showed significant correlation for tumor stage outside the Milan criteria and histologically moderate or poorly differentiated HCC [30] .…”
Section: Case 1 -Evolutionmentioning
confidence: 99%